Governança corporativa: os mecanismos e órgãos de controle estão alinhados com o estágio do ciclo de vida organizacional? - Perin, Luciana Todero (Universidade do Vale do Rio dos Sinos, 2020)
The adoption of Good Corporate Governance Practices presupposes, first of all, efficient control mechanisms and bodies, without which it would be incoherent to start the journey of implementing an effective Governance System. The company needs to know the effectiveness and reliability that these controls provide and if they are compatible with its life cycle. In this context, the present work has the general objective of identifying whether the degree of maturity of the control mechanisms and organs is aligned with the stage of the organizational life cycle. The adopted method included a mixed approach, with non-probabilistic and intentional cross-sectional sampling, characterized in terms of its nature as applied research and the technical procedures included a questionnaire, adapted from Necik (2008), with a seven-point Likert scale, in a sample of 27 privately held companies. The data indicate that companies grow, evolve in their life cycle stage and the controls do not always follow this evolution, as indicated by the results presented, as 74.1% of the analyzed companies had controls inferior to their life cycle stage. Additional analyzes indicate that the relationship between the life cycle stage and the degree of maturity of the controls also has no direct interference with the size of the company, age, net income, tax environment, number of employees, legal nature and business activity. On the other hand, a factor that improved this relationship was the company having External Audit, not all audited companies have controls compatible with their stage of the life cycle, but all companies that have controls compatible with or superior to their stage of the life cycle life are audited. This finding demonstrates the important role of the Audit in the search for continuous improvement of control mechanisms and bodies in companies. However, the great barrier that needs to be overcome is to assimilate that governance is not an external seal that can be obtained and that it will cover the company like a mantle. It is exactly the opposite, there is a long way to go and the first step will always have to be taken internally.
Keywords: Auditoria; Controles; Estágio do ciclo de vida; Governança corporativa; Audit; Controls; Life cycle stage; Corporate governance; ACCNPQ::Ciências Sociais Aplicadas::Direito